O relevo na interpretação da variabilidade espacial dos teores de nutrientes em folha de citros - de Leao, Marisol G. A. [UNESP]; Marques Junior, Jose [UNESP]; de Souza, Zigomar M.; Siqueira, Diego S. [UNESP]; Pereira, Gener Tadeu [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2010)
Foliar diagnosis is a method for assessing the nutritional status of agricultural crops, which helps in the understanding of soil fertility and rationalized application of fertilizers taking into account economic and environmental criteria. The study aimed to use the landrelief as criteria to assist in interpreting the spatial variability of nutrient content of the citrus leaf. The leaves were collected at regular intervals of 50 m, totaling 332 sampling points. Data were analyzed by descriptive statistics, geostatistics and induction of decision tree. With the aid of digital elevation model (MDE) and the profile planaltimetric, the area was divided into three different landrelief and sub-strands. The highest values for nutrients from the leaves of citrus were observed at the top (concave area) segments on a half-slope and lower slope. The nutrients from the citrus leaves showed high values of correlation (above 0.5) with the altitude of the study area. The technique of geostatistics and the induction of decision tree show that the relief is the variable with the greatest potential to interpret the maps of spatial variability of nutrients from the citrus leaves.
Landrelief in the interpretation of spatial variability of nutrient content in citrus leaves
Keywords: orange; Kriging; data mining; soil-landscape relationship